Nurses’ perception of the applicability of the continuity of care process - Rojas Manzano, Karen Liseth; Toro Delgado, Nicolay; Eraso Riascos, Deysi Johana; Mondragón-Sánchez, Edna Johana (Revista Cuidarte, 2022)
Introduction:The continuity of care (CC) is understood as the adaptation of caregivers and their support network to the new health-disease situation. Objetive:To understand nurses’ perception of the applicability of the continuity of care process. Materials and methods: Study with a qualitative and phenomenological approach. The subjects of the study were nurse coordinators. Semi-structured interviews were conducted. Atlas.ti was used for data analysis. Results: The participants partially applied continuity of care due to a lack of clarity of the concept, disconnection between primary health care and specialized care, and administrative limitations. The continuity of care is practiced in a disorganized and empirical manner. Discussion: There is a clear need for implementing communication strategies between the different levels of care to strengthen teamwork and promote patient self-care. According to the participants, the information is not shared among the different levels of care, hindering the continuity of patient care. Conclusions: The application of the continuity of care process is fragmented and disorganized. Based on evidence from other countries, the participants recognized that if continuity of care were applied in Colombia, it would improve the quality of services and the quality of life of patients. How to cite this article: Rojas-Manzano Karen Liseth, Toro-Delgado Nicolay, Eraso-Riascos Deysi Johana, Mondragón-Sánchez Edna Johana. Percepción de los profesionales de enfermería sobre la aplicabilidad del proceso de continuidad de cuidados. Revista Cuidarte. 2023;14(1):e2210.http://dx.doi.org/10.15649/cuidarte.2210